Spaces of interdisciplinary in/congruity: the coming together of engineers and social scientists in planning for sustainable urban environments - Hadfield-Hill, Sophie; Horton, John; Kraftl, Peter; Balestieri, José Antônio Perrella [UNESP]; Vilanova, Mateus Ricardo Nogueira [UNESP]; Dias, Rubens Alves [UNESP]; Soares, Paulo Valladares [UNESP] (Taylor & Francis, 2020)
In the context of a globalised interdisciplinary moment, where boundary-crossing research collaborations are valorised, this paper considers encounters between multidisciplinary researchers. Presenting empirics and reflections from an international project where social scientists and engineers sought to collaborate, communicate and address complex challenges associated with sustainable urban development, we question a series of assumptions about interdisciplinary research. Importantly, we pause to consider the practical implications of doing this work. In particular, we draw attention to the spaces of interdisciplinarity, from the field to the lab and the meeting room, the role of researchers’ reflexivity and positionality, and the importance of being aware of the embodied, emotional realities of such work. In so doing, we call for more critical, evidence-based reflection upon the lived in/congruities of interdisciplinary practices.
Keywords: embodied; emotion; engineers; Interdisciplinary; social scientists; space; sustainable urban development